Betty Hard White Wheat - Sears, Rollin G.; Martin, T. Joe; Shroyer, James P. (My University, 1999)
An informational publication about Betty Hard White Wheat, a new wheat variety developed cooperatively by the Kansas Agricultural Experiment Station and the Agriculture Research Service, United States Department of Agriculture.
L917_1999-05
Keywords: L917; Crops; L